Small intestinal biopsy and resection in standing sedated horses. (22nd April 2016) - Coomer, R.; McKane, S.; Roberts, V.; Gorvy, D.; Mair, T.
Summary: Diagnostic laparotomy and laparoscopy are surgical techniques commonly used for the investigation of chronic abdominal disease and weight loss. They can both be usefully carried out in the standing sedated horse, allowing a thorough examination of the dorsal abdominal cavity and biopsies to be harvested. Small intestinal disease is an important cause of weight loss and recurrent colic. Inflammatory or neoplastic bowel disease may not always be apparent grossly and histopathological assessment of full thickness biopsies may be required to provide a definitive diagnosis. Details of cases of 15 horses that underwent small intestinal biopsy or enterectomy while sedated and standing are presented. Three incisional infections occurred causing delayed wound healing. Three horses were subjected to euthanasia before hospital discharge: two had persistent gastric reflux and one had colitis. A further six were subjected to euthanasia in the first 4 months due to their underlying inflammatory bowel condition. One horse was subjected to euthanasia for severe laminitis that was presumed to be caused by treatment with a corticosteroid 4 years later, and one died of acute colic 2.3 years after successful resection and anastomosis. Five horses were alive at the time of review, median 2.7, range 1.2–4.3 years. Overall therefore, 3 (20%) horses died during hospitalisation and 5 (33%) were still alive at the end of the study. Results from this series suggest that minimising the number of intestinal biopsies may reduce morbidity, but the underlying pathological process appears to be the most important prognostic factor for survival. Resection and anastomosis in the standing sedated horse proved feasible.